Study Komparasi antara Metode Contextual Teaching Learning (CTL) dengan Metode Ceramah Tanya Jawab terhadap Hasil Belajar PAI Siswa SMK PGRI 9 NGAWI - AZIZ NURI SATRIYAWAN AZIZ (Jurnal Al-Qalam: Jurnal Kajian Islam & Pendidikan, 2020)
The purpose of this study was (1) to know the learning outcomes of PAI using the CTL method with the question and answer lecture method of SMK PGRI 9 Ngawi 2016/2017 Academic Year, (2) find out teh significant difference between the CTL method with the question and answer lecture method towards PAI learning outcomes of vocational students PGRI 9 NGAWI Academic Year 2016/2017. The form of this research is quantitative research to look for evidence of hypotheses, while this research strategy uses a comparative approach which is a study that aims to find evidence of whether there is a difference between two variables and if there is significant or on difference. In this study the population being the same as the research sample were all students of class X as many as 40 students, which were divided inti 2 classes, namely : TKR class X as many as 20 students and class X TKJ as many as 20 students. The result showed that first, the PAI learning outcomes of students using the CTL method were better than the Question and Answer Lecture method. This is shown based on the average value of the CTL method of 19.00 higher than the average value of the Question and Answer Lecture method of 13.70, secondly, there is a significant difference berween students’ PAI learnng outcomes using the CTL method and the Question and Answer Lecture Method. This is shown based on the calculation results obtained t count 2.10 is greater thah t table with a significance level of 5% of 2.021.Keywords : Learning Outcomes, Contextual Teaching and Learning, Question and Answer Lecture